Application of The Student Active Learning (SAL) Model Based on Local Wisdom to Improve Critical Thinking in Primary School - Azmi, Nurradiatun; Mahsul, Alwan; Syudirman, Syudirman (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2026)
This study was motivated by the low critical thinking skills of fourth-grade students at SDN Inpres Doridungga in IPAS subjects, with only 39% of students achieving learning completeness. This problem is caused by conventional learning methods that have not integrated the context of students' lives, especially local wisdom values. This study aims to improve students' critical thinking skills through the application of the Student Active Learning (SAL) model based on the local wisdom of Bima Regency. The research method used is Kurt Lewin's Classroom Action Research (CAR) model, which was carried out in two cycles. The research subjects were 18 fourth-grade students, consisting of 10 male students and 8 female students. The research instruments included observation sheets, critical thinking skills tests, and student response questionnaires The research findings indicate an improvement in students’ critical thinking skills from Cycle I to Cycle II, with the mastery rate increasing from 17% in Cycle I to 79% in Cycle II, thereby meeting the established mastery target. The integration of the local wisdom of Rimpu Bima, Uma Lengge, and Mbolo Weki in learning proved to be effective in creating meaningful, contextual learning that was able to activate students. This study concludes that the Student Active Learning model based on local wisdom can improve students' critical thinking skills in IPAS subjects.